2009
DOI: 10.1002/jca.20185
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe amitriptyline intoxication with plasmapheresis

Abstract: Tricyclic antidepressant poisoning is one of the most common causes of serious intoxication. Here, we report a 2-year-old girl with severe amitriptyline (70 mg/kg) intoxication. She was in comatose, had generalized tonic clonic seizure, ventricular tachycardia, and wide QRS complexes. Although she did not respond to classical therapies, very good clinical response to plasmapheresis was obtained and she developed no complications. Thus, plasmapheresis may be an effective treatment modality in poisoning with dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In patients in whom no response to certain and traditional treatments is obtained, improvement with plasmapheresis occurs (2,3,4). In native and foreign publications, it has been reported that plasmapheresis is efficient in life-threatening tricyclic antidepressant (amitriptyline) intoxications in children (2,3,4,8,9,10). The consciousness opened after plasmapheresis in our patients whose Glascow coma scores were found to be 4 at presentation.…”
Section: Discussionmentioning
confidence: 52%
“…In patients in whom no response to certain and traditional treatments is obtained, improvement with plasmapheresis occurs (2,3,4). In native and foreign publications, it has been reported that plasmapheresis is efficient in life-threatening tricyclic antidepressant (amitriptyline) intoxications in children (2,3,4,8,9,10). The consciousness opened after plasmapheresis in our patients whose Glascow coma scores were found to be 4 at presentation.…”
Section: Discussionmentioning
confidence: 52%
“…From the initial 1312 studies obtained, 77 studies met the inclusion criteria, including 1 observational study , 5 animal studies , 4 in vitro studies , 4 pharmacokinetic (PK) studies , and 63 case reports , 39 of which had sufficient toxicokinetic (TK) data. In total, 108 patients were included for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with life threatening amitriptyline intoxication successful results had been reported with plasma exchange had been (7,(18)(19)(20)(21). Recently one study reported successful result with extended high cut-off dialysis (9).…”
Section: Discussionmentioning
confidence: 99%